The Role of CTAB Surfactant Composition on the Structural and Magnetic Properties of Mn0.5Zn0.5Fe2O4 Ferrofluid for Energy Harvesting Devices - Wa Ode Umratul Khazanah; Arif Hidayat; Ahmad Taufiq; ST. Ulfawanti Intan Subadra (Universitas Negeri Malang, 2024)
Concerns about environmental damage caused by pollution and the use of non-renewable energy sources have driven many researchers to explore sustainable energy-harvesting materials. This study successfully developed an energy harvester based on Mn0.5Zn0.5Fe2O4 ferrofluid. Notably, Cetyl Trimethyl Ammonium Bromide (CTAB) was used as the surfactant in the synthesis of the Mn0.5Zn0.5Fe2O4 ferrofluid via the coprecipitation method. The CTAB mass was varied at 0, 0.25, 0.5, 0.75, and 1 gram, labeled as MZC0, MZC0.25, MZC0.5, MZC0.75, and MZC1. XRD patterns showed that MZC0 have a cubic spinel structure, while CTAB addition altered the structure to monoclinic, following CTAB’s pattern. FTIR spectra at 418.1, 571.1, and 445.3 cm⁻¹ confirmed Mn–O, Fe–O, and Zn–O stretching, indicating successful spinel formation. Meanwhile, FTIR bands at 2800 and 2900 cm⁻¹ in MZC0.25–MZC1 samples were due to C–H stretching from CTAB. VSM analysis revealed a decreasing saturation magnetization (Ms) with increasing CTAB. SEM images confirmed surfactant coating on nanoparticles. Energy harvesting tests showed output voltages of -0.4 to 2.9 V and low induced currents (0.3–1.9 μA), suggesting the potential of Mn0.5Zn0.5Fe2O4/CTAB-based ferrofluid as an eco-friendly energy harvester.